Kynurenine Relaxes Arteries of Normotensive Women and Those With Preeclampsia. Issue 11 (3rd March 2021) - Worton, Stephanie A.; Pritchard, Harry A.T.; Greenwood, Susan L.; Alakrawi, Mariam; Heazell, Alexander E.P.; Wareing, Mark; Greenstein, Adam; Myers, Jenny E.
Abstract : Supplemental Digital Content is available in the text. Abstract : Rationale: Activation of the kynurenine pathway of tryptophan catabolism by infection and inflammation contributes to the development of systemic hypotension. Commercially-available kynurenine has direct vasorelaxant effects on arteries from several species and reduces systemic blood pressure when administered to normotensive or hypertensive rats. Objectives: To determine whether kynurenine promotes relaxation of human resistance arteries from normotensive and hypertensive pregnant women and to identify the vascular mechanism of its effects. Methods and Results: In isolated omental and myometrial resistance arteries from normotensive pregnant women, kynurenine (1 mmol/L) significantly reduced U46619-induced constriction (omentum N=14, P =2.4×10 −3 ; myometrium N=21–25, P =2.6×10 −4 ) and relaxed preconstricted arteries (N=53, P =1.0×10 −11 ; N=20, P =8.8×10 −3 ). Vasorelaxation persisted following endothelium removal (N=7, P =1.6×10 −4 ) but was completely prevented by inhibition of large-conductance Ca 2+ -activated K + channels (BKCa ) channels with iberiotoxin (N=9, P =5.7×10 −4 ) or paxilline (N=10, P =2.1×10 −17 ). Accordingly, in isolated vascular smooth muscle cells from omental arteries, kynurenine increased the BKCa current (n=5–8, P =0.022) and the amplitude of spontaneous transient outward currents (n=6, P =0.031) but did not affect spontaneous transient outward current frequency. Kynurenine also increased Ca 2+ spark frequency of pressurized omental arteries (n=8, P =0.031). Vasorelaxant effects of kynurenine persisted following inhibition of ryanodine receptors (N=7, P =0.48) but were moderately reduced by inhibition of adenylate cyclase (N=9, P =0.024). In arteries from women with preeclampsia, kynurenine similarly attenuated vasoconstriction (N=15, P =1.3×10 −5 ) and induced BKCa -mediated vasodilation (N=16, P =2.0×10 −4 ). Vasorelaxation in response to kynurenine and a specific BKCa activator, NS11021, was absent in fetal-derived placental resistance arteries in normal pregnancy and preeclampsia. Conclusions: Kynurenine dilates systemic arteries from multiple territories via BKCa activation. Notably, the vasorelaxatory capacity of kynurenine is preserved in preeclampsia, suggesting this approach may have translational potential for the treatment of hypertension in pregnancy. The data warrant further investigation of the potential to exploit this endogenous vasorelaxant as a new treatment for hypertensive pathologies.